2022
DOI: 10.2166/wh.2022.101
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Pseudomonas aeruginosa isolated from hospital wastewater in the Czech Republic

Abstract: Resistant bacteria may leave the hospital environment through wastewater. The opportunistic pathogen Pseudomonas aeruginosa, due to its intrinsic resistance to many antibiotics and its ability to easily acquire antibiotic resistance determinants, poses a significant threat to public health. The aim of this study was to evaluate the antibiotic resistance profiles of cultivated P. aeruginosa in untreated hospital effluents in the Czech Republic. Fifty-nine P. aeruginosa strains isolated from six hospital wastewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In this study carried out by Kiyaga et al [ 28 ], it was revealed that there was a 31% prevalence of MDR strains among the P. aeruginosa isolates, and this rise in prevalence reflects the global trend of increasing MDR P. aeruginosa infections [ 29 ]. Numerous studies provide further evidence of the escalating problem of antibiotic resistance in P. aeruginosa infections [ 30 , 31 , 32 ]. Unfortunately, the antibiotics that were once effective in treating these infections have now become ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…In this study carried out by Kiyaga et al [ 28 ], it was revealed that there was a 31% prevalence of MDR strains among the P. aeruginosa isolates, and this rise in prevalence reflects the global trend of increasing MDR P. aeruginosa infections [ 29 ]. Numerous studies provide further evidence of the escalating problem of antibiotic resistance in P. aeruginosa infections [ 30 , 31 , 32 ]. Unfortunately, the antibiotics that were once effective in treating these infections have now become ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Further MDR strains were observed for E. coli, P. aeruginosa, A. baumannii, and K. pneumoniae, while the three other species were almost exclusively found to be XDRs (Figure 4). Several studies have reported MDR Gram-negative bacteria from environmental sources where their resistance pattern was established using disk diffusion according to either EUCAST 51,52 or Clinical and Laboratory Standards Institute (CLSI) guidelines. [53][54][55][56] The high incidence of extensively…”
Section: Discussionmentioning
confidence: 99%
“…Further MDR strains were observed for E. coli , P. aeruginosa , A. baumannii , and K. pneumoniae , while the three other species were almost exclusively found to be XDRs ( Figure 4 ). Several studies have reported MDR Gram-negative bacteria from environmental sources where their resistance pattern was established using disk diffusion according to either EUCAST 51 , 52 or Clinical and Laboratory Standards Institute (CLSI) guidelines. 53–56 The high incidence of extensively drug-resistant strains in both clinical and nonclinical wastewaters may be attributed to the constant selective pressure placed on the bacteria not only by the excessive use of antibiotics but also by other antimicrobial agents that are released from hospitals and other urban runoffs, eg, industrial and agricultural effluent.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa (P. aeruginosa ) is a Gram‐negative bacterium that is considered to be an opportunistic pathogen [136] . This bacterium is a ubiquitous microorganism that is responsible for a variety of serious infections such as nosocomial infections, wound and soft tissue infections, and urinary tract infections, in patients who has compromised immune system or comorbidities [137] . To combat P. aeruginosa infections, ciprofloxacin, a type of fluoroquinolone antibiotic, has been used extensively due to its effectivity against P. aeruginosa [138] .…”
Section: Antimicrobial Pdt In Bacterial Infectionsmentioning
confidence: 99%
“…[136] This bacterium is a ubiquitous microorganism that is responsible for a variety of serious infections such as nosocomial infections, wound and soft tissue infections, and urinary tract infections, in patients who has compromised immune system or comorbidities. [137] To combat P. aeruginosa infections, ciprofloxacin, a type of fluoroquinolone antibiotic, has been used extensively due to its effectivity against P. aeruginosa. [138] As such, this antibiotic is still of utmost importance in treating P. aeruginosa infections.…”
Section: Ciprofloxacin-resistant Pseudomonas Aeruginosamentioning
confidence: 99%